1991
DOI: 10.1085/jgp.97.6.1187
|View full text |Cite
|
Sign up to set email alerts
|

Multiple conductance states of the light-activated channel of Limulus ventral photoreceptors. Alteration of conductance state during light.

Abstract: A B S T R A C T The properties of light-dependent channels in Limulus ventral photoreceptors have been studied in cell-attached patches. Two sizes of single-channel events are seen during illumination. Previous work has characterized the large (40 pS) events; the goal of the current work was to characterize the small (15 pS) events and determine their relationship to the large events. The small events are activated by light rather than as a secondary result of the change in membrane voltage during light. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In Limulus, small, light-dependent channel openings have also been described (Bacigalupo and Lisman, 1983;Nagy 1990;Nagy and Stieve, 1990). Johnson et al (1991) reported that the incidence of small events tends to become higher sometime after light onset, and suggested that transition from large to small events could contribute to the decreased amplitude of the photocurrent during the slow phase of light adaptation. A quantitative analysis of such apparent nonstationary behavior is difficult, particularly without voltage-clamping the cell (see Discussion).…”
Section: Msmentioning
confidence: 96%
See 2 more Smart Citations
“…In Limulus, small, light-dependent channel openings have also been described (Bacigalupo and Lisman, 1983;Nagy 1990;Nagy and Stieve, 1990). Johnson et al (1991) reported that the incidence of small events tends to become higher sometime after light onset, and suggested that transition from large to small events could contribute to the decreased amplitude of the photocurrent during the slow phase of light adaptation. A quantitative analysis of such apparent nonstationary behavior is difficult, particularly without voltage-clamping the cell (see Discussion).…”
Section: Msmentioning
confidence: 96%
“…In the bottom part of the figure a segment of the recording was expanded, and straight lines with slopes of 50 and 17 pS were fitted to the large and the small events, respectively. scheme involving slowly changing gating modes (Johnson, Bacigalupo, Vergara, and Lisman, 1991). Unfortunately, while small-amplitude, light-induced openings were observed on many occasions, the presence of muhiple channels in those patches precluded statistical analysis.…”
Section: Msmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures for obtaining gigaseals on the R-segment membrane are similar to those described for experiments on the R-lobe of ventral photoreceptor cells (Johnson et al, 1991). The patch electrodes used were fabricated from Corning #7052 glass (Garner Glass, Claremont, CA), coated with Sylgard, and firepolished.…”
Section: Patch Recordings R-segmentmentioning
confidence: 99%
“…We have been able to make whole-cell recordings from isolated cells and have found that their responses to light are similar to those of cells in vivo, and that currents recorded under voltage clamp in the dark resemble currents recorded with the two-electrode voltage clamp in ventral photoreceptor cells (Lisman et al, 1982). We have also been successful in making gigaseals onto both the rhabdomeral membrane of the R-segment and the arhabdomeral membrane of the A-segment in isolated cells (Chamberlain & Barlow, 1984): voltage-activated channel activity can be observed in patches of A-segment membrane, while patches of R-segment membrane contain light-activated channels which resemble those observed in the light-sensitive membrane of ventral photoreceptors (Bacigalupo & Lisman, 1983;Nagy & Stieve, 1990;Johnson et al, 1991).…”
Section: Introductionmentioning
confidence: 99%